Toward sustainable production of value‐added bioenergy and industrial oils in oilseed and biomass feedstocks. Issue 10 (13th August 2021) - Park, Kiyoul; Sanjaya, Sanju A.; Quach, Truyen; Cahoon, Edgar B.
Abstract: Plant fatty acids are used for food, feed, fuel, and industrial materials. Structurally and chemically diverse fatty acids, referred to as unusual or specialized fatty acids, are found in the seed oils of diverse plant species. Many unusual fatty acids have potential use as alternative and renewable sources of biofuels and bio‐based industrial feedstocks due to their variant structures' physical or functional properties. Oils enriched in these fatty acids can increase the value of oilseed crops and provide co‐products that can be readily extracted from lignocellulosic materials in biomass crops. Here, we describe recent progress in strategies for enhancement of oil production and quality in oilseed crops and the extension of this knowledge for metabolic engineering of biomass crops. Successful implementation of these strategies, in part, through the use of emerging synthetic biology tools, will provide added product value for the economic sustainability of biomass crops as bioenergy feedstocks. Abstract : Triacylglycerols (TAGs), the principal component of plant vegetable oils, are energy‐dense storage forms of fatty acids that can function as feedstocks for biofuels and bioproducts. The value of TAGs for these non‐food applications can be enhanced by the introduction of unusual fatty acids with structural modifications that expand vegetable oil functionalities. This review describes efforts to uncover the biochemistry associated with the production of TAGs enriched in unusual fatty acids and the use of this knowledge for synthetic biology‐based engineering of these pathways in seeds and vegetative tissues of biomass crops.